2015
DOI: 10.1051/0004-6361/201526653
|View full text |Cite
|
Sign up to set email alerts
|

3D pyCloudy modelling of bipolar planetary nebulae: Evidence for fast fading of the lobes

Abstract: Aims. The origin and evolution of the shapes of bipolar planetary nebulae are poorly understood. We postulate that their history can be traced through their internal velocity fields in a procedure similar to the one well established for spherical objects. Such an analysis requires 3D photoionization and kinematical modelling that is computationally very time consuming. We apply an axially symmetric pseudo-3D photoionization model, pyCloudy, to derive the structures of six bipolar nebulae and two suggested post… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Assuming V exp (AGB) = 16 − 22 km s −1 (corresponding to the observed expansion velocity of the cold CO gas, Bachiller et al 1993;Bergstedt 2015), V exp (today) = 12 km s −1 (from the [N ii] line; Arias & Rosado 2002), and R IB = 55 ′′ (the ion-ization front radius), the dynamical age would be roughly 7100 − 8600 yrs. Gesicki et al (2016) suggested t dyn ≃ (5/7) × (R IB /V exp ) based on hydrodynamical model calculations. Adopting V exp = 12 km s −1 as above, the hydrodynamical age would be 7140 yrs.…”
Section: Amorphous Silicate Grain Modelmentioning
confidence: 99%
“…Assuming V exp (AGB) = 16 − 22 km s −1 (corresponding to the observed expansion velocity of the cold CO gas, Bachiller et al 1993;Bergstedt 2015), V exp (today) = 12 km s −1 (from the [N ii] line; Arias & Rosado 2002), and R IB = 55 ′′ (the ion-ization front radius), the dynamical age would be roughly 7100 − 8600 yrs. Gesicki et al (2016) suggested t dyn ≃ (5/7) × (R IB /V exp ) based on hydrodynamical model calculations. Adopting V exp = 12 km s −1 as above, the hydrodynamical age would be 7140 yrs.…”
Section: Amorphous Silicate Grain Modelmentioning
confidence: 99%
“…The effect of the geometry on the determination of the velocity fields from line profiles have been studied by Morisset & Stasinska (2008). By fitting imaging with 3D models and high resolution profiles with expansion velocities Gesicki et al (2016) determine dynamical properties of 8 PNe. One must notice the long standing effort of the Potsdam group to develop hydrodynamical photoionization models: emission line profiles are used by Schönberner et al (2014) to constrain 1D models of the expansion properties and the internal kinematics of PNe.…”
Section: Nebular Kinematicmentioning
confidence: 99%
“…This is in line with the fact that higher percentage of nebula is covered by the slit during our observation of PC 19 compared to PB 1. More observations at different slit positions and a 3D photoionization model (e.g., Gesicki et al 2016) may help to yield more precise results.…”
Section: Summary and Discussionmentioning
confidence: 99%